2019
DOI: 10.7717/peerj.6528
|View full text |Cite
|
Sign up to set email alerts
|

Revision of the Afro-Madagascan genus Costularia (Schoeneae, Cyperaceae): infrageneric relationships and species delimitation

Abstract: A recent molecular phylogenetic study revealed four distinct evolutionary lineages in the genus Costularia s.l. (Schoeneae, Cyperaceae, Poales). Two lineages are part of the Oreobolus clade of tribe Schoeneae: the first being a much-reduced genus Costularia s.s., and the second a lineage endemic to New Caledonia for which a new genus Chamaedendron was erected. The other two lineages were shown to be part of the Tricostularia clade of tribe Schoeneae. Based on morphological and molecular data, the genus Costula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Oreobolus Clade: Larridon et al (2018a) found that Costularia s.l. was composed of four distinct evolutionary lineages with two lineages being part of the Oreobolus Clade: (i) a much‐reduced genus Costularia (Larridon et al, 2019a) and (ii) a small New Caledonian endemic genus Chamaedendron . The circumscription of the other genera in this clade (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Oreobolus Clade: Larridon et al (2018a) found that Costularia s.l. was composed of four distinct evolutionary lineages with two lineages being part of the Oreobolus Clade: (i) a much‐reduced genus Costularia (Larridon et al, 2019a) and (ii) a small New Caledonian endemic genus Chamaedendron . The circumscription of the other genera in this clade (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Costularia includes 15 species, 11 of which are endemic to Madagascar (Larridon et al, 2018, Larridon et al, 2019). Most species grow in high elevation ericoid vegetation.…”
Section: Discussionmentioning
confidence: 99%
“…The Oreobolus Clade of tribe Schoeneae is the only clade with an important in situ radiation in Madagascar associated with a positive shift in diversification rates. The Oreobolus Clade includes Costularia which is largely endemic to Madagascar (Larridon et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although much taxonomic work remains at the species level, we have a good understanding of species diversity per genus and the geographic distribution of species (Jung et al 2016;Semmouri et al 2019;Muasya and Larridon 2021;Larridon 2022a). However, in the case of Madagascar, the only taxonomic treatment of the family, Chermezon's Flore de Madagascar, dates from 1937, although research has been done since then on a few genera (Díaz et al 2019;Larridon et al 2019), the taxonomic treatment of the Cyperaceae of Madagascar Table 1. Overview of the genera occurring in Madagascar and their subfamily and tribal placement following Larridon et al (2021b), and ordered according to Larridon (2022a).…”
Section: Introductionmentioning
confidence: 99%